A Study on Road Network Structure of Fezzan Region - Ahmed M. Alhodairi (Journal of Pure & Applied Sciences, 2018)
This paper studies and analyzes the road network of Fezzan region, its structure, accessibility, connectivity and detour.  In order to achieve the study objectives the Geographic Information System (GIS) and the Network Analyzer programs were used. The results showed differences in-between the agglomerations in attaining the accessibility and connectivity. In addition, the limited spread of the road network throughout the vicinity of Fezzan has lowered its ratio to the total land area and the population. This raised the need to review possibilities of restructuring the road network so that it could help improving potentiality of reaching the various places of Fezzan.